2007
DOI: 10.1097/01.tp.0000251430.11723.b6
|View full text |Cite
|
Sign up to set email alerts
|

Association Between C4d Staining in Renal Transplant Biopsies, Production of Donor-Specific HLA Antibodies, and Graft Outcome

Abstract: We demonstrated a significant association between diffuse C4d staining, production of DSA, and graft failure. Although the concurrent detection of DSA and C4d positivity is uncommon in our patients, these results indicate that outcome in this group is poor and they may benefit from therapies directed at the humoral response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 28 publications
7
57
0
1
Order By: Relevance
“…2,3,9,10,13,14 Lower prevalence of C4d positivity has been reported in indication biopsies, as in the Acute pathologic changes other than rejection and normal biopsies were grouped as NR category. Twenty one percent of these biopsies stained positively for C4d, a prevalence that did not differ from other series, 9,10,13,18 independently of the technique employed. However, it is not possible to exclude that in some of these first biopsies with acute graft injury C4d deposits preceded the development of cellular or ABMR, that would be later diagnosed in subsequent biopsies, 21 which were not done in our study.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…2,3,9,10,13,14 Lower prevalence of C4d positivity has been reported in indication biopsies, as in the Acute pathologic changes other than rejection and normal biopsies were grouped as NR category. Twenty one percent of these biopsies stained positively for C4d, a prevalence that did not differ from other series, 9,10,13,18 independently of the technique employed. However, it is not possible to exclude that in some of these first biopsies with acute graft injury C4d deposits preceded the development of cellular or ABMR, that would be later diagnosed in subsequent biopsies, 21 which were not done in our study.…”
Section: Discussionmentioning
confidence: 74%
“…2,3,[8][9][10][11]18 So far, the pathogenic and clinical significance of those findings is incompletely understood. Humoral and cellular alloresponses might affect the kidney graft either independently or concurrently, with endothelium antigens of capillaries and arteries acting as targets for both humoral and cellular immune responses, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because of the retrospective nature of the study, presence of DSAs at the time of biopsy was not measured. However, earlier studies repeatedly showed that C4d staining was strongly related to DSAs (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The conventional immunofluorescence panel of immunoglobulin and complement components has been replaced by the detection of C4d, a single complement degradation product that can independently predict unfavorable graft outcome. [7][8][9][10][11][12][13][14] C4d participates in the classic pathway of complement activation. Activated C4 is cleaved to C4a and C4b.…”
mentioning
confidence: 99%